DOI: 10.18174/515697
|View full text |Cite
|
Sign up to set email alerts
|

Best of both worlds : Co-producing climate services that integrate scientific and indigenous weather and seasonal climate forecast for water management and food production in Ghana

Abstract: acknowledge your amazing role in my PhD life my Marilyn Dede Nyadzi Attoh. Finally, but most importantly, I would like to express the depth of my love and gratitude to Anne Selasi Tofoatsi for her encouragement and continued support along this journey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 243 publications
(374 reference statements)
2
17
0
Order By: Relevance
“…In line with our results, many previous studies found that coproduction is an efficient way to reach out to and engage smallholder farmers and build trust and user confidence [16,21,28]. Consistent with the literature, our results suggest that capacity building is essential to the success of coproduction [16,17,58].…”
Section: Evaluation Of the Coproduction Experimentssupporting
confidence: 92%
“…In line with our results, many previous studies found that coproduction is an efficient way to reach out to and engage smallholder farmers and build trust and user confidence [16,21,28]. Consistent with the literature, our results suggest that capacity building is essential to the success of coproduction [16,17,58].…”
Section: Evaluation Of the Coproduction Experimentssupporting
confidence: 92%
“…In Ghana, too, these obstacles affect smallholder farmers' access to, reliance on and use of WCIS in farm decision-making (Yaro, 2013, Codjoe et al, 2014, Nyadzi, 2020. Many Ghanaian farmers still rely mainly on local or traditional knowledge to make decisions on farm operations.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in today's context of increasing weather and climate variability, farmers need improved knowledge to base their responses to uncertainties regarding the weather and climate (Codjoe et al, 2014, Nyadzi, 2020.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations